2008
DOI: 10.1136/hrt.2008.146738
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of therapeutic strategies for ST-segment elevation acute myocardial infarction: the impact of a territorial network on reperfusion therapy and mortality

Abstract: Organisation of a territorial network for STEMI is associated with increased rates of reperfusion therapy and reduction of in-hospital and 1-year mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 30 publications
3
16
0
1
Order By: Relevance
“…As indicated by our findings, such organisation of care increases accessibility of reperfusion therapy (by increasing the rate of primary PCI) among STEMI patients and reduces mortality in this patient population. Similarly to our study, Saia et al [14] showed that introduction of regional primary PCI network was associated with an increased rate of reperfusion therapy among STEMI patients by increasing the proportion of patients treated with primary PCI, while the rate of fibrinolytic therapy was reduced. Introduction of this treatment network was also associated with a mortality reduction.…”
Section: Discussionsupporting
confidence: 86%
“…As indicated by our findings, such organisation of care increases accessibility of reperfusion therapy (by increasing the rate of primary PCI) among STEMI patients and reduces mortality in this patient population. Similarly to our study, Saia et al [14] showed that introduction of regional primary PCI network was associated with an increased rate of reperfusion therapy among STEMI patients by increasing the proportion of patients treated with primary PCI, while the rate of fibrinolytic therapy was reduced. Introduction of this treatment network was also associated with a mortality reduction.…”
Section: Discussionsupporting
confidence: 86%
“…Improvements in the door-to-balloon time in itself were also shown to be poorly correlated with acute outcomes in a report from the Get With The Guidelines programme. 21 This observation is consistent with the impressive absolute 6.5 and 5.7% reduction in acute mortality observed in the Wien and Bologna STEMI registries, 22,23 respectively, after a 21 and 18% increase in the rate of reperfusion had been achieved, mostly by primary PCI, much larger than expected on the sole basis of superiority of primary PCI over fibrinolysis, verified in meta-analysis of randomized controlled trials that demonstrated only a 2% absolute reduction in mortality. 24 Simply striving to achieve a higher use of reperfusion in population with STEMI may impact total mortality more than other initiatives (e.g.…”
Section: Discussionsupporting
confidence: 73%
“…Les dernières recommandations de l'ESC insistent sur la nécessité de créer des réseaux régionaux pour adapter ces algorithmes aux circonstances locales [8]. Ceux-ci permettraient une augmentation de la proportion de patients bénéficiant d'une reperfusion, une diminution des délais de reperfusion, et une diminution de la mortalité [9,10].…”
Section: Introductionunclassified